Improvement of hydrodeoxygenation stability of nickel phosphide based catalysts by silica modification as structural promoter. (15th September 2017) - Liu, Xuguang; Li, Zhenyu; Zhang, Baoquan; Hu, Maocong
Graphical abstract: Highlights: SiO2 added to Ni2 P based catalysts as structural promoter. Life of catalyst with modification was prolonged to three times of the unmodified one. SiO2 retarded the transformation of the active phase Ni2 P. Carbon deposition originating from metallic nickel was reduced with SiO2 addition. Abstract: This study proposed a novel and facile approach to promote the stability of nickel phosphide (Ni2 P) based catalysts by adding silica (SiO2 ) as structural promoter under hydrothermal condition. Catalytic hydrodeoxygenation (HDO) of triglyceride using soybean oil as model feed over Ni2 P and palladium supported on α-Al2 O3 (Ni2 PPd/α-Al2 O3 ) with and without SiO2 addition was conducted. With SiO2 modification, the catalyst was stable for 144 h which is three times of that from the unmodified one, while higher than 99.0 wt.% conversion was achieved with green diesel (i.e., C15-18 alkane) as the main products. H2 -TPD, NH3 -TPD, and XRD over fresh catalysts proved that SiO2 addition exhibited no distinguished effect on hydrogen chemisorption ability and active phase. XRD, TEM, XPS, EDX, XRF, H2 -TPR, N2 physisorption, and TG/IR over fresh or/and spent catalysts demonstrated that SiO2 was a structural stability promoter (spacer), hindering the transformation of the active phase Ni2 P. Furthermore, carbon deposition during the HDO process due to exist of metallic nickel was reduced with SiO2 addition. This work demonstrated that Ni2 P supported on α-Al2 O3 modified by SiO2 (Ni2 PPd-SiO2 /α-Al2 O3 ) was a promising catalyst for the hydrodeoxygenation (HDO) of triglyceride to produce green diesel. With further work, it may lead to a catalyst capable for HDO in industry.